Attention Deficit Hyperactivity Disorder and Treatment Adherence in Adolescent Acne Patients: Investigating the Relationship for Better Care Strategies - Koç, Huriye Aybüke; Altınöz Güney, Cansu; Önal, Bedia Sultan (Dermatology Practical & Conceptual, 2025)
Introduction: Accompanying comorbidities in acne vulgaris (AV) patients affect treatment adherence. Objectives: The purpose of this study was to investigate the relationship between treatment compliance and attention deficit hyperactivity disorder (ADHD) in adolescents with AV. Methods: This study included 140 patients with AV. At the beginning of the treatment, each patient's acne severity was assessed, and the Conners-Wells' Adolescent Self-Report Scale-Long Form (CASS-L) was administered. The Morisky Medication Adherence Scale (MMAS-8) was used to assess treatment adherence. The treatment response was assessed using a six-point scale. Results: Significant differences were found in the scores on the 10 subscales of the CASS-L among the 3 groups. The Global Acne Grading System (GAGS) scores showed a positive correlation with the scores of the subscales of the CASS-L, with 3 of them at a moderate level and 7 at a weak level. Five MMAS subscales had a weak correlation and 5 had a moderate correlation with the CASS-L subscale scores. The 9 subscales and the treatment response showed a slight negative correlation. Conclusion: ADHD is one of the many psychiatric comorbidities that frequently coexist with acne vulgaris. Its treatment is long-term and achieving a good treatment response relies heavily on patient adherence. Our study, which showed a decrease in acne treatment adherence and response as ADHD symptoms increased, will raise awareness among dermatologists to be more vigilant in their approach to this patient group.